2016
DOI: 10.1007/s10511-016-9445-6
|View full text |Cite
|
Sign up to set email alerts
|

Approximate Solution to the Fractional Second-Type Lane-Emden Equation

Abstract: Abstract.The spherical isothermal Lane-Emden equation is a second order non-linear differential equation

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Nowadays, generalizations of some of the basic differential equations in physics led to new and more deep insight to the macroscopic phenomena in a wide range of areas like anomalous diffusion, signal processing and quantum mechanics (Podlubny 1999;Sokolov et al 2002;Kilbas et al 2006;Laskin 2000). In astrophysics, El-Nabulsi (2011) considered a fractional equation of state for white dwarf stars; Bayian and Krisch (2015) have investigated the fractional versions of the stellar structure equations for non-radiating spherical objects, Abdel-Salam and Nouh (2016) and Nouh and Abdel-Salam (2017) introduced a series solution to the fractional isothermal and polytropic gas spheres and obtained a solution converges to the surface of the sphere with a few series terms when compared with the solution of the integer one.…”
mentioning
confidence: 99%
“…Nowadays, generalizations of some of the basic differential equations in physics led to new and more deep insight to the macroscopic phenomena in a wide range of areas like anomalous diffusion, signal processing and quantum mechanics (Podlubny 1999;Sokolov et al 2002;Kilbas et al 2006;Laskin 2000). In astrophysics, El-Nabulsi (2011) considered a fractional equation of state for white dwarf stars; Bayian and Krisch (2015) have investigated the fractional versions of the stellar structure equations for non-radiating spherical objects, Abdel-Salam and Nouh (2016) and Nouh and Abdel-Salam (2017) introduced a series solution to the fractional isothermal and polytropic gas spheres and obtained a solution converges to the surface of the sphere with a few series terms when compared with the solution of the integer one.…”
mentioning
confidence: 99%
“…The results for the radii, masses, and central density of the conformable models are listed in Table 2. We observed that the conformable fractional models have less volume and less mass than both the integer models and the fractional models computed based on the scheme presented by Abdel-Salam and Nouh (2016). The dramatic change in both the mass and radius of the models indicate the huge compression of the material inside the star.…”
Section: Resultsmentioning
confidence: 72%
“…The fractional Emden functions ( R u ) computed by Abdel-Salam and Nouh (2016) are plotted (dashed lines) along with the conformable one ( . This may come from the difference in the nature between the conformable and the mRFD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations